2022
DOI: 10.1029/2021jg006317
|View full text |Cite
|
Sign up to set email alerts
|

Energetically Informed Niche Models of Hydrogenotrophs Detected in Sediments of Serpentinized Fluids of the Samail Ophiolite of Oman

Abstract: A geochemical gradient established by mixing between reduced, hyperalkaline (pH > 11), H2‐rich fluids generated through the process of serpentinization and surrounding surface water (pH ∼ 8) in the Samail Ophiolite of Oman provides an opportunity to characterize the geochemical and biological factors that influence the distribution of H2 oxidizing chemotrophs, hydrogenotrophs. In this study, 16S rRNA gene amplicon sequencing was implemented to characterize hydrogenotrophs in sediments underlying surface expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 92 publications
1
35
0
Order By: Relevance
“…Determining whether or not systems at temperatures below ∼120°C reflect equilibrium in marine settings is further complicated by biological consumption. Microbiomes in the actively altering system may be consuming H 2 to fuel their metabolism (Canovas et al., 2017; Howells et al., 2022; Miller et al., 2018; Rempfert et al., 2017; Suzuki et al., 2014; Wankel et al., 2011). The downward pointing arrows in Figure 9 indicate the extent to which hydrogenotrophic metabolism may be active at Von Damm and Lost City.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining whether or not systems at temperatures below ∼120°C reflect equilibrium in marine settings is further complicated by biological consumption. Microbiomes in the actively altering system may be consuming H 2 to fuel their metabolism (Canovas et al., 2017; Howells et al., 2022; Miller et al., 2018; Rempfert et al., 2017; Suzuki et al., 2014; Wankel et al., 2011). The downward pointing arrows in Figure 9 indicate the extent to which hydrogenotrophic metabolism may be active at Von Damm and Lost City.…”
Section: Resultsmentioning
confidence: 99%
“…Serpentinizing systems, established when aqueous planetary fluids react with ultramafic (UM) rocks, produce significant quantities of dihydrogen (H 2 ) across a large range of geochemical conditions. This H 2 actively supports chemosynthetic communities on Earth (Charlou et al., 2002; Douville et al., 2002; Hodgkinson et al., 2015; Howells et al., 2022; D. S. Kelley et al., 2005; McDermott, 2015; Proskurowski et al., 2008; Reeves et al., 2014; Schmidt et al., 2007, 2011; Seyfried et al., 2011, 2015), and has done so since early in Earth's history, likely reaching back to the emergence of life as we currently understand it more than 3.5 Gya (G. J. Dick, 2019; Fuchs, 2011; Herschy et al., 2014; Humphris & Klein, 2017; Keir, 2010; D. S. Kelley et al., 2001; Lane et al., 2010; McCollom & Bach, 2009; Sleep et al., 2004; Weiss et al., 2016; Wood, 1991). The mineral inventory of chondritic material in the meteorite record indicates that serpentinizing systems are not limited to Earth (McSween et al., 1991; Watters & Prinz, 1979; Weisberg & Kimura, 2012), leading to suggestions of serpentinization in other solar systems (Hinkel & Unterborn, 2018; Putirka & Rarick, 2019; Thiabaud et al., 2015).…”
Section: Introductionmentioning
confidence: 92%
“…This overall topic is the subject of 24 of the papers in this Special Issue (Bernasconi et al, 2021;Cook, Blank, Rietze, et al, 2021;Cooperdock et al, 2020;de Obeso et al, 2021;Ellison et al, 2021;O. Evans et al, 2020;Hong et al, 2022;Howells et al, 2022;Katayama et al, 2020;Kelemen et al, 2021;Leong et al, 2021;Malvoisin et al, 2020;Monnin et al, 2021;Nothaft, Templeton, Boyd, et al, 2021;Nothaft, Templeton, Rhim,…”
Section: Introductionmentioning
confidence: 99%
“…A supportive community of researchers has grown around these topics, embodied in part by the annual Serpentine Days conferences in Europe. This overall topic is the subject of 24 of the papers in this Special Issue (Bernasconi et al., 2021; Cook, Blank, Rietze, et al., 2021; Cook, Blank, Suzuki, et al., 2021; Cooperdock et al., 2020; de Obeso et al., 2021; Ellison et al., 2021; O. Evans et al., 2020; Hong et al., 2022; Howells et al., 2022; Katayama et al., 2020; Kelemen et al., 2021; Leong et al., 2021; Malvoisin et al., 2020; Monnin et al., 2021; Nothaft, Templeton, Boyd, et al., 2021; Nothaft, Templeton, Rhim, et al., 2021; Renard, 2021; Sabuda et al., 2021; Schwarzenbach, Vogel, et al., 2021; Schwarzenbach, Vrijmoed, et al., 2021; Templeton et al., 2021; Ternieten et al., 2021a, 2021b; Yoshida et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial organisms inhabit environmental niches with a wide range of oxidation–reduction (redox) conditions. Molecular studies and genomic analyses have revealed the great diversity of enzymatic functions that occur along redox gradients (Gutiérrez‐Preciado et al, 2018; Vigneron et al, 2022), and there is growing recognition that the energetics of biochemical reactions that support microbial metabolism are affected by the geochemical context (Alain et al, 2022; Canovas & Shock, 2020; Howells et al, 2022). However, proteins, in addition to performing catalytic functions, are chemical entities in their own right.…”
Section: Introductionmentioning
confidence: 99%